ORANG BUANGAN (BANNELINGEN) PADA PERKEBUNAN PALA DI KEPULAUAN BANDA (Paramita: Historical Studies Journal, 2010)
Placement of the exiles who run the nutmeg plantations on the Banda Islands is another way to run the economic system. Empowerment of the exiles as labor becomes a distinct advantage for the government or plantation owners. Economically exiles cannot be sold, but they can be used as production workers in the plantation or for those who have skills they can be employed to build and create a variety of facilities on the estate. Disposal of this person basically is never lost from time to time. In modern reign, the removal of human rights is often done just that with the term and a more subtle treatment of exiled. In the old order and the new order, areas such as Maluku Seram, Banda, Buru Island, Masohi, Namlea still just be a dumping ground for people who are considered guilty, and they are now more famous by the term political prisoners or prisoners. In the subsequent exiles are then settled and have contributed to the progress of his new country such as introducing rice cultivation and irrigation, but this needs further research. Keywords: an exile, plantation of pala, Banda   Penempatan orang buangan yang menjalankan perkebunan pala di Kepulauan Banda adalah cara lain untuk menjalankan sistem ekonomi. Pemberdayaan orang buangan sebagai tenaga kerja menjadi keuntungan tersendiri bagi pemerintah atau pemilik perkebunan. Secara ekonomis, orang buangan tidak dapat dijual, tetapi mereka dapat digunakan sebagai pekerja produksi di perkebunan atau bagi mereka yang memiliki keterampilan mereka bisa digunakan untuk membangun dan menciptakan berbagai fasilitas di perumahan. Pembuangan dari orang ini pada dasarnya tidak pernah hilang dari waktu ke waktu. Dalam pemerintahan modern, pemindahan hak asasi manusia sering melakukan hal itu dengan istilah dan pengobatan yang lebih halus diasingkan. Dalam orde lama dan orde baru, beberapa kawasan seperti Maluku Seram, Banda, Pulau Buru, Masohi, Namlea masih saja menjadi tempat pembuangan bagi orang-orang yang dianggap bersalah, dan mereka sekarang lebih terkenal oleh para tahanan politik. Dalam buangan berikutnya kemudian menetap dan telah memberi kontribusi pada kemajuan negara baru seperti memperkenalkan budidaya padi dan irigasi, namun hal ini perlu penelitian lebih lanjut. Kata kunci: buangan, perkebunan pala, Banda